Gonçalo M. Tavares: o despojamento da razão como interrogação da impossibilidade
One of the most particular features of O Senhor Valéry, from Gonçalo M. Tavares, is the originality of its creative processes, along the line of the homage trend underlying the architecture of “The neighbourhood”. Investing on the centrality of a unique main character, the author builds fictional spaces where he recreates the main features of the summoned authors, with surprisingly meaningful results. This study aims at analysing the innovative way in which the author puts together a logic reduced to its core and close to children’s reasoning, which Rachel Caiano’s illustrations, with their minimalist and primitive traits, underline. The absurd is present all throughout the work and is centred on the utmost extravagance of the character, who perceives and defines his world trough an egocentric geometry and geography, projected on the text’s own structure, layout and illustrations.